VD_FINDINFO Décision / 2014 / 1050 vom 24. November 2014 - VD Tribunal cantonal (2014)
UNITÉ DE LA PROCÉDURE, DISJONCTION DE CAUSES, PRINCIPE DE LA CÉLÉRITÉ | 29 CPP (CH), 30 CPP (CH), 393 al. 1 let. a CPP (CH)